Powered by Happy - Thomas, Beth (Rawalpindi Services Book Club)
he only pocket-sized book packed with ways to boost not only workplace happiness, but also your-and your company's-performance Research has shown that employee happiness improves the bottom line, but how can a time-crunched, stressed-out employee wedge in a little joy? Instrumental for anyone working, whether in a cubicle or a corner office, Powered by Happy offers a quick hit of optimism for the workday, which will help your career. Employee engagement expert Beth Thomas has crafted a powerful little book filled with upbeat coaching, practical advice, and proven techniques. "Powered by Happy provides a step by step, tip by tip strategy for figuring out what gives us joy and how to create an environment in which we can find it-all day, every day, in any situation, no matter what challenges we face."--Larry Israelite, talent management executive "Here is a practical collection of strategies and approaches that will support and enliven the lives of employees and managers." -Elliott Masie, chair, The Learning Consortium "Look hard into the mirror, be honest with yourself, follow Beth's advice, and become more productive and honestly happy!" -Steven M. Lyman, vice-president, American Eagle Outfitters
Include References
Keywords: a